2017
DOI: 10.1016/j.heares.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noise exposure and musical training on suprathreshold auditory processing and speech perception in noise

Abstract: Recent animal research has shown that exposure to single episodes of intense noise causes cochlear synaptopathy without affecting hearing thresholds. It has been suggested that the same may occur in humans. If so, it is hypothesized that this would result in impaired encoding of sound and lead to difficulties hearing at suprathreshold levels, particularly in challenging listening environments. The primary aim of this study was to investigate the effect of noise exposure on auditory processing, including the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
112
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(145 citation statements)
references
References 81 publications
18
112
2
1
Order By: Relevance
“…Moreover, we did not find a significant pairwise correlation between any of these behavioural and objective measures. This accords with recent large-cohort studies that have not found a correlation of proposed measures of cochlear synaptopathy to the lifetime noise exposure of the participants or their speech-in-noise perception 37,71,72 . This may suggest that either cochlear synaptopathy has little influence on auditory difficulty or that it has no significant prevalence, at least in normal-hearing people.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we did not find a significant pairwise correlation between any of these behavioural and objective measures. This accords with recent large-cohort studies that have not found a correlation of proposed measures of cochlear synaptopathy to the lifetime noise exposure of the participants or their speech-in-noise perception 37,71,72 . This may suggest that either cochlear synaptopathy has little influence on auditory difficulty or that it has no significant prevalence, at least in normal-hearing people.…”
Section: Discussionsupporting
confidence: 91%
“…That sub-clinical variability in audiometric thresholds at these frequencies might predict speechin-noise perception has often been overlooked: Several previous studies have assumed that subclinical variability in audiometric thresholds do not contribute to speech-in-noise perception and have not explored this relationship (e.g., Alvord, 1983;Kumar et al, 2012). Of those that have tested the relationship, two found a correlation (Schoof and Rosen, 2016;Yeend et al, 2017), although one of these (Yeend et al, 2017) included participants with mild hearing loss and it is possible that these participants were responsible for the observed relationship. Two others found no correlation but restricted the variability in their sample by either imposing a stringent criterion on 'normal' hearing less than 15 dB HL or considering only young participants aged 18-30 years (Oberfeld and Klöckner-Nowotny, 2016).…”
Section: Central Contributions To Speech-in-noise Performancementioning
confidence: 99%
“…Although the OSHA regulations do not require testing at 8 kHz or above, poorer high-frequency hearing has been reported in workers exposed to occupational noise. Deficits have been reported within the extended high-frequency (EHF) range of 10 kHz and above in workers exposed to occupational noise (Hallmo, Borchgrevink, and Mair 1995;Korres et al 2008;Riga et al 2010;Mehrparvar et al 2014), personal audio system device users (Le Prell et al 2013;Sulaiman, Husain, and Seluakumaran 2015;Kumar et al 2017), those with a history of musical training (Schmidt et al 1994;Gonçalves et al 2013;Liberman et al 2016), frequent concert goers (Grose, Buss, and Hall 2017), those with acoustic trauma during military service (Balatsouras, Homsioglou, and Danielidis 2005;Buchler, Kompis, and Hotz 2012) and individuals with higher lifetime noise exposure (Prendergast et al 2017a;Yeend et al 2017). NIOSH recommends testing through 8 kHz.…”
Section: Audiometric Monitoring For Occupational Noise-induced Hearinmentioning
confidence: 99%